KOMUNIKASI ANTARBUDAYA MASYARAKAT SUKU DUANO (SUKU LAUT) DENGAN MASYARAKAT SUKU BUGIS DI KECAMATAN TANAH MERAH KABUPATEN INDRAGIRIHILIR - Abd Basir; Yasir " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Comunication and culture have a perfect relationship, in this case that can see a observation from comunication of intercultural society of Duanu and Celebes tribe in Tanah merah regency. The population of duanu tribe is minority so that they think that have diference perception, so some of them rarely interact with other cultures especially Celebes because Duanu does not usually interact each other. The purpose of this observation is to know the concept betwen Duanu and celebes and process of adaptation knowing whether the obstruction of comunication of intercultural society of Duanu and celebes.The method used is qualitatif method by using Purpose sampling. Collecting data is done by observation, interview and documentation. The process of analysis data is to begin with simbolik interaction and the sample of this research are eight people. It consists four from duanu and four from celebes. Analysis data used is reduction data. Persentation and verification data or drawing the conclusion.From this research, the concept the society of Duanu and bugis, Duanu perceived is one of the tribes having coarse and hard tribe toward celebes tribe, but some of them said they are soft tribe and the same with another, yet the environment make it course tribe because they are used to at sea and interact using a loud voice in order to hearing message each other, and environment factor make his black skin and , the contrary the perception of Duanu tribe with celebes that celebes is revenge atitude and the interaction of Duanu is open minded another on the contrary, the intercaction of celebes toward Duanu joining with some activities made by Duanu, but the problem is like language, stereotip, and prejudice.From this research, the concept the society of Duanu tribe and bugis tribe, Duanu tribe perceived is one of the tribes who have coarse and hard tribe toward Bugis tribe, but some of them said that they are soft tribe and the same with another tribe, yet the environment make it course tribe because they are used to at sea and interact using a loud voice in order to hearing he message each other, and environment factor make his black skin and big body, on the other hand the perception of Duanu tribe with Bugis that Bugis is revenge atitude and the interaction of Duanu tribe is open minded another tribe on the contrary the intercaction of Bugis toward Duanu joining with some activities which is made by Duanu, but the problem is like language, stereotip, and prejudice.Keywords: Intercultural Comunication, Duanu Buginese tribe.